Treatment of disability in the self-regulatory framework of the Spanish media - Gómez, Yordhana; Martín Llaguno, Marta; Castellet, Andreu (Historia y Comunicación Social, 2014)
Social integration models of disability have undergone an evolution reinforced by the International Convention on the Rights of Persons with Disabilities. In accordance with the concepts of disability and accessibility defined by the Convention, this research aims to find out if the Spanish media offer due, specific treatment to these issues. To achieve our research goal, we undergo a content analysis of the stylebooks of 5 major Spanish media –newspapers and news agencies.